2014
DOI: 10.1038/mi.2014.29
|View full text |Cite
|
Sign up to set email alerts
|

T helper cell IL-4 drives intestinal Th2 priming to oral peanut antigen, under the control of OX40L and independent of innate-like lymphocytes

Abstract: Intestinal T helper type 2 (Th2) immunity in food allergy results in IgG1 and IgE production, and antigen re-exposure elicits responses such as anaphylaxis and eosinophilic inflammation. Although interleukin-4 (IL-4) is critically required for allergic sensitization, the source and control of IL-4 during the initiation of Th2 immunity in vivo remains unclear. Non-intestinal and non-food allergy systems have suggested that natural killer-like T (NKT) or γδ T-cell innate lymphocytes can supply the IL-4 required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 37 publications
1
86
2
Order By: Relevance
“…We and others have shown that OX40L on DCs is responsible for DC-mediated Th2 skewing and sensitization in the gastrointestinal tract (25,26,55). In the current studies, OX40L neutralization had only a minor inhibitory effect on DC-driven Th2 cytokine production in vitro and in vivo, indicating that other mechanisms for DC-driven Th2 priming must predominate in the skin.…”
Section: Discussionmentioning
confidence: 62%
“…We and others have shown that OX40L on DCs is responsible for DC-mediated Th2 skewing and sensitization in the gastrointestinal tract (25,26,55). In the current studies, OX40L neutralization had only a minor inhibitory effect on DC-driven Th2 cytokine production in vitro and in vivo, indicating that other mechanisms for DC-driven Th2 priming must predominate in the skin.…”
Section: Discussionmentioning
confidence: 62%
“…The activating dendritic cells do not provide decisive IL-4 [22]. Instead, it has been argued that Th2 induction results from a combination of antigen dose, select costimulatory molecules and the deliberate inhibition of conflicting signals, such as IL-12, that drive alternative T cell differentiation [19,[23][24][25][26][27]. Other innate cell types, such as basophils, may also enter the lymph node early in the immune response and provide polarising IL-4 signals [28][29][30][31].…”
Section: Initiation Of the Th2 Responsementioning
confidence: 96%
“…The expression of OX40L was examined because it has been implicated in Th2-related allergic responses (Blázquez & Berin, 2008;Chu et al, 2014;Gauvreau et al, 2014). The mRNA expression of OX40L in the duodenum was enhanced in the OVA group ( Fig.…”
Section: Effects Of L Murinus On Il-12 Production and Ox40 Ligand (Omentioning
confidence: 99%
“…In addition to cytokine-dependent regulations, T cell differentiation is also influenced by co-stimulatory molecules expressed by dendritic cells (DC). For example, OX40 ligand (OX40L) has been linked to the development of Th2-related allergic responses (Blázquez & Berin, 2008;Chu et al, 2014;Gauvreau et al, 2014).…”
Section: Introductionmentioning
confidence: 99%